System Development Of Parallel Robot With Industrial Controller - Mohd Ameeraldeen , Mohd Salleh (UTeM, 2010)
The 4-DOF Zlatonov and Gosselin platform parallel robot is the further invention follows by the Stewart-Gough Platform. The Stewart-Gough Platform is a spatial mechanism in which a moving platform is connected to a fixed base with six extensible limbs by spherical joints. The Zlatonov and Gosselin platform is capable to manipulate the performance as the Stewart-Gough Platform but in fewer axes presented. First, this project report will introduce over view of variety types of robot, especially the parallel robot and the device that are being developed. Then, it is follow by the introduction of the basic of concept for the 4-DOF Zlatonov and Gosselin platform parallel robot. In this section the declaration of the objectives, the scopes of the project, the problems statement and the expected outcome will be state. It was discussed the study has been done of the 4-DOF Zlatonov and Gosselin platform parallel robot. The Methodology used to solve the design and fabrication problem is depending by using the CAD/CAM SolidWorks software. The fabrications processes involved in this project where to build 4-DOF platform robot station with motors attachment. The motors controlled by its drive using PLC device. Finally, the complete improvement design of 4-DOF Zlatonov and Gosselin platform parallel robot is presented in 3D modeling by using SolidWorks. After that is follow by some suggestion and recommendation for this project.